(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2020)
The main objective of the current study is to evaluate the relationship between earnings, its components and earnings valuation and, at the same time, to assess the impact of audit quality on these variables of companies listed on the Tehran Stock Exchange. The data used in this study were collected for a sample of 141 listed companies on the Tehran Stock Exchange from 2010 to 2016. Research hypotheses were analyzed using panel data by means of the panel method. Research findings indicated no relationship between earnings, its components and earnings valuation. By analyzing the effect of audit quality variables, we have also observed that audit firm size has a positive and significant effect on the relationship between earnings, its components and earnings valuation. Moreover, the obtained results substantiated the positive and significant effect of auditor tenure on the relationship between earnings, total discretionary accruals, operational cash flow, non-discretionary accruals, and earnings valuation. In addition, findings revealed that auditor industry specialization has a negative and significant effect on the relationship between earnings, its components and earnings valuation. The study aims to investigate the mediating effect of audit quality on the relationship between earnings and earnings valuation in Iran, so the outcomes of the current study may be helpful to the developing nations.